COMPLETION OF SERVICE BILL OF LADING ISSUED FOR CUSTOMER SATISFACTION - Denny J. Najoan; Esti Legesi (Institut Transportasi dan Logistik Trisakti, 2015)
PT. Tresnamuda Sejati, as one of the manufacturer export documents, is always trying to serve neat and clean work for their customers. To keep their customers loyal in the competition era, they try their best to satisfy them. Customers’ satisfaction is one of the important things in running the company. In order to do so, the company should evaluate all the employees’ performance especially employees who are handling the customers. This study is aimed at finding out the employees’ performance of PT. Tresnamuda Sejati in satisfying the customers. The methods used are combination of quantitative and qualitative. Likert Scale and Cartesius are used to find out the performance indicators. The result of this study shows that their employees do not perform well and do not fulfill the indicators. The employees’ performance needs to be improved especially performance related to responsiveness and assurance.